Multivariate optimization of ultrasound-assisted liquid-liquid microextraction based on two solvents for cadmium preconcentration prior to determination by flame atomic absorption spectrometry - Ferreira, Vanessa Jesus; Jesus, Marina Santos de; Santos, Mayara Costa dos; Guedes, Wesley N. [UNESP]; Lemos, Valfredo A.; Novaes, Cleber G.; Costa, Floriatan Santos; Pacheco, Clissiane S. Viana; Silva, Erik Galvao Paranhos da; Amorim, Fabio Alan Carqueija (Royal Soc Chemistry, 2021)
A method based on ultrasound-assisted emulsification liquid-liquid microextraction (USAEME) for cadmium determination by flame atomic absorption spectrometry (FAAS) was developed in this work. USAEME is based on the use of the mixture of 1,2-dichloroethane and trichloroethylene as an acceptor phase, 2-(2-bromo-5-pyridylazo)-5(diethylamino)phenol (Br-PADAP) as a chelating reagent, and ethanol as a dispersive solvent. The composition of the extraction and dispersive solvents, the volume of the extraction solvent, pH, and the sonication time were optimized using the multivariate strategy. The limits of detection and quantification calculated under optimum conditions were, respectively, 0.39 and 1.33 mu g L--1,L- and the obtained enrichment factor was 21. The accuracy was tested by the analysis of certified reference materials. The method was applied to cadmium determination in bivalve mollusks, water, and urban wastewater from Pontal Bay, Bahia, Brazil. The proposed method is simple, fast, and efficient, and uses small amounts of organic solvents for the determination of cadmium.